The Role of Canva-Based Learning Media to Motivate Students to Participate in Islamic Religious Education Learning at Mts Muhammadiyah 15 Medan - Shoumi, Putri Nur; Zahriani Jf, Nurul (FKIP - Universitas Riau, 2025)
This study aims to analyses the role of Canva-based learning media in motivating students to participate in Islamic Religious Education (PAI) learning at MTS Muhammadiyah 15 Medan. Canva-based learning media offers the convenience of presenting material that is engaging, interactive, and tailored to students' needs. This research method uses a qualitative descriptive approach by collecting data through interviews, observations, and documentation. Data analysis is carried out in the stages of data reduction, data presentation, and conclusion drawn. The results show that the use of Canva-based media can increase students' interest in learning, create a more dynamic learning atmosphere, and make it easier to understand the material. Thus, Canva-based media can be an innovative solution in increasing students' motivation to learn, especially in lPA subjects.